Penggunaan Media Pembelajaran Interaktif Berbasis Wordwall Untuk Meningkatkan Kemampuan Literasi Di SMK Swasta Bersama Berastagi - Elisabeth Margareta; Monalisa Hutagaol; Lian Yesika Hutasoit; Cindi Sitinjak; Betesda Lumban Gaol (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Implementation of Community Activities (PkM) is a program carried out by FKIP students at HKBP Nommensen University, Medan. Program for implementing Wordwall-based interactive learning media to improve literacy skills at SMKS Bersama Berastagi. In the learning process, supporting media is needed to help implement the interactive teaching and learning process in the classroom. The media chosen is adapted to the situation and conditions existing in the school, therefore it is deemed appropriate to use Wordwall media to help facilitate the teaching and learning process in the classroom. Interactive learning is inviting students to involve thinking, seeing, hearing and skills at the same time, one of which is while writing. Wordwall is an alternative choice from various types of interactive learning media that can make the learning process fun and not boring for students and teachers. This application aims to be a fun learning resource, media and assessment tool for students. So the results of using wordwall-based interactive learning media increase literacy skills. In this way, students' literacy skills at Berastagi Private Vocational School can increase and by using wordwall learning media it can be made more interesting and varied. Then students' enthusiasm for learning will increase and it won't be boring.